Antimicrobial activity test of the crude extracts of some marine Mollusca against selected pathogenic fungi, in vitro - Zainab Dakhil (University of Thi-Qar Journal of Science, 2019)
Crude extracts of marine Mollusca Sepia sp. ,Tibia insulaechorab-curta and Thais sp.marked as A, B and C respectively, using 50 % acetic acid were studied for their antifungalactivity using agar well diffusion technique against seven fungi (Aspergillus niger, A. flavus,Candida albicans , C. krusei, C. tropicalis , C. famata & C. guilliermondii ). No antifungalactivity was recorded against A. niger &A. flavus in all concentrations of Thais sp. extract.Sepia sp. & Tibia insulaechorab-curta extracts exhibited significant differences (P≥0.05) togood antifungal activity more than Thais sp. extract. An extract has been showed high activityagainst C. albicans (inhibition zone=27.6 mm) diameter, and minimum zone of inhibition(16mm) was recorded against growth A. niger of same extract. In B extract, maximuminhibition zone (26.6mm ) in growth A. flavus & C. albicans and minimum inhibition zonediameter (15mm) in growth A. niger .Also the minimal inhibitory concentration of all extractswere detected .The results showed the inhibition zones diameter of Fluconazole as positivecontrol approximately with the inhibition zones of crude extracts .